2021
DOI: 10.3390/educsci11010022
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in Science Education. A Systematic Review of the Literature

Abstract: The implementation of gamification in education has attracted many researchers to increase engagement and achieve learning more effectively. Implementing technology in science curricula has seen a massive influx over the past years to stop the decline in students’ motivation towards science learning and promote scientific thinking. This study’s objective is to present the empirical findings of the state-of-the-art literature on the use of gamification in science education. Therefore, we performed a systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
249
0
35

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(303 citation statements)
references
References 126 publications
19
249
0
35
Order By: Relevance
“…The findings were used to form a depression diagnosis model based on a gamification technique to ensure continuous adolescent engagement. It is consistent with a previous study [51] that the use of the gamification method boosts students' motivation and engagement and contributes positively to the growth of adolescents' interest and attitudes at schools [18].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings were used to form a depression diagnosis model based on a gamification technique to ensure continuous adolescent engagement. It is consistent with a previous study [51] that the use of the gamification method boosts students' motivation and engagement and contributes positively to the growth of adolescents' interest and attitudes at schools [18].…”
Section: Discussionsupporting
confidence: 92%
“…Challenges are the critical element in improving adolescent intrinsic motivation, while rewards and feedback elements can satisfy the adolescents' intrinsic feelings. These marks are also consistent with another study, suggesting that a well-designed gamification application, integrating emerging game mechanics and game components, helped increase motivational outcomes [51].…”
Section: Correlation Between Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…As motive we consider anything that encourages a person to act and it is believed that it affects the reasons and the way of human behavior, learning and achievement (Kalogiannakis, Papadakis & Zourmpakis, 2021). Motivation is distinguished in intrinsic and extrinsic; intrinsic motivation urges a person to engage in a task, the completion of which is an end in itself and it aims at the personal satisfaction and development and is related to academic achievement and self-efficacy, while extrinsic motivation is the positive or negative reinforcement which is created by the students' background and puts them into action (Bye, Pushkar & Conway, 2007;Kalogiannakis, Papadakis & Zourmpakis, 2021). It is imperative for the teacher to know which kind of motivation to use so that the students perform better (Kalogiannakis, Papadakis, & Zourmpakis, 2021).…”
Section: Motivation Towards Science Educationmentioning
confidence: 99%
“…Science education is considered an essential portion of 21st-century education [15]; despite this, some issues need to be considered, such as students' motivation toward science and their difficulty comprehending scientific concepts, especially abstract ones. Some studies have demonstrated that students' misconceptions can affect their understanding and learning achievements [16][17][18][19][20][21][22]. Moreover, some countries have revealed a weakness among their students in science outcomes following the Program for International Student Assessment and the Trends in International Mathematics and Science Study (TIMSS) [20][21].…”
Section: Introductionmentioning
confidence: 99%